PROVINCE ANALYSIS OF FINANCIAL MANAGEMENT OF VILLAGE FUNDS IN IMPROVING THE COMMUNITY ECONOMY IN FATUULAN VILLAGE, KIE DISTRICT, SOUTH CENTRAL TIMOR DISTRICT – NTT - Deetje Wieske Manuain; Nonce. F. Tuati; Hana Paulina Wetang (Jurnal Ekonomi, 2023)
The implementation of autonomy at the lowest level of government is the Village. Villages can be said to be the spearhead of national development because they are sources of strength and resilience for the national government. Managing Village Funds is regulated based on Minister of Home Affairs Regulation Number 113 of 2014 concerning Village Financial Management. Village funds are one component of transfer income which is part of village finances so that their management follows the village financial management mechanism. Village funds are a tool to help implement village governance, village development and community empowerment in an effort to improve the community economy. With this village fund , it is hoped that it can help the community in terms of needs, development of facilities and infrastructure, and can develop local economic potential based on the conditions and potential of the village. This research was conducted using qualitative descriptive analysis methods. This method is carried out by creating a systematic, factual and accurate picture or painting of the facts, properties and relationships between the phenomena being investigated. Data collection was carried out by interviews and collecting factual data in accounting information data processing procedures and connecting with existing theoretical data. The results of the research show that the management of village funds has been running quite effectively, although the allocation is not yet 100% effective, where there are many village development activities (physical) carried out which help farmers and the community in carrying out daily activities, where the poverty level has begun to decline in Fatuulan Village. Community empowerment programs and activities to improve the community's economy have been implemented but are still not on target, but in general the community in Fatuulun Village has felt an improvement in the community's economy. The output of this research is the implementation of financial management of village funds in improving the economy of the people of Fatuulan Village, Kie District, South Central Timor Regency, NTT. Which will be published in the proceedings of the 2023 International Conference on Applied Science and Technology (iCAST) or SINTA accredited national journal articles with a minimum rank of 4. The proposed research TKT is TKT 3.